A series of new lanthanide fumarates displaying three types of 3-D frameworks. Issue 12 (19th February 2016) - Tan, Xiao-Feng; Zhou, Jian; Fu, Lianshe; Xiao, Hong-Ping; Zou, Hua-Hong; Tang, Qiuling
Abstract : A series of 3-D new lanthanide fumarates obtained by hydrothermal reaction can be classified into three types, according to the crystal structures, which are related to lanthanide contraction. Abstract : A series of lanthanide fumarates [Sm2 (fum)3 (H2 fum)(H2 O)2 ] (1, H2 fum = fumaric acid), [Ln2 (fum)3 (H2 O)4 ]·3H2 O {Ln = Tb (2a ), Dy (2b )} and [Ln2 (fum)3 (H2 O)4 ] {Ln = Y (3a ), Ho (3b ), Er (3c ), Tm (3d )} were prepared by the hydrothermal method and their structures were classified into three types. The 3-D framework of compound1 contains a 1-D infinite [Sm–O–Sm] n chain built up from the connection of SmO8 (H2 O) polyhedra sharing edges via three –COO group bridges of fumarate ligands, which is further constructed into a 3-D network structure with three kinds of fumarate ligands. Compounds2a–b are isostructural and consist of a 3-D porous framework with 0-D cavities for the accommodation of chair-like hexameric (H2 O)6 clusters. Compounds3a–d are isostructural and have a 3-D network structure remarkably different from those of1 and2a–b, due to the different coordination numbers for the Ln 3+ ions and distinct fumarate ligand bridging patterns. A systematic investigation of seven lanthanide fumarates and five reported compounds revealed that the well-known lanthanide contraction has a significant influence on the formation of lanthanide fumarates. The magnetic properties of compounds1, 2b and3b–3d were also investigated.